Polyethylene microplastics increases the tissue damage caused by 4-nonylphenol in the common carp (Cyprinus carpio) juvenile - Ammar, Esraa; Mohamed, Mahmoud S.; Sayed, Alaa El-Din H. (Frontiers in Marine Science, 2022)
Plastic particles have the ability to transfer harmful chemical pollutants due to their high adsorption capacity. Therefore, this study aimed to investigate the effects of combined exposure to polyethylene microplastics (PE-MPs) and 4-nonylphenol (4-NP) on juvenile common carp (Cyprinus carpio) using histopathological and histochemical biomarkers. Fish were separated into a control group and three treatment groups (10 mg/L PE-MPs; 10 mg/L PE-MPs + 200 µg/L 4-NP; 200 µg/L 4-NP) for a two-week continuous exposure experiment followed by two weeks of recovery. The three treatment groups showed histopathological changes compared to the control. These alterations included severe edema, lifting of the outer epithelium, interlamellar fusion and vacuolation, secondary lamellar shortening and complete fusion, increased mucous cell numbers in the gill tissue, enlargement of inner layer stratum periventricular, cell degeneration with pyknotic nuclei, increased blood capillaries, spongiosis in the brain tissue (optic tectum), central vein hemorrhage, shrunken and fatty degeneration of hepatocytes, rosette shapes around small congested blood sinusoids, vacuoles, necrosis, and severe glycogen reduction in the liver tissue. Some tissue changes improved during the two-week recovery period but did not return to normal. In conclusion, the mixture exposure of the PE-MPs and 4-NP on fish carp induced some histological alterations in most studied tissues and post-exposure made improvement in cellular and tissue structure.